Molecular profiling of crude oil by using Distillation Precipitation Fractionation Mass Spectrometry (DPF-MS). (15th December 2018) - Yerabolu, Ravikiran; Kotha, Raghavendhar R.; Niyonsaba, Edouard; Dong, Xueming; Manheim, Jeremy M.; Kong, John; Riedeman, James S.; Romanczyk, Mark; Johnston, Cliff T.; Kilaz, Gozdem; Kenttämaa, Hilkka I.
Graphical abstract: Abstract: Molecular profiling of crude oil is a tremendous challenge due to its inherent complexity. An accurate molecular fingerprint of a crude oil may facilitate rational design of crude oil recovery efforts, such as enhanced oil recovery, improve the efficiencies of the refining processes, and enable a better assessment of the value of the crude oil. Herein, a new approach (Distillation Precipitation Fractionation Mass Spectrometry (DPF-MS) method) is introduced for the molecular level characterization of crude oil. This method involves the separation of crude oil into six fractions followed by high-resolution mass spectral analysis optimized for each individual fraction. The separation methods are distillation, precipitation, and fractionation in an auto column followed by solid phase extraction. Initially, the fractions were examined by using Fourier transform infrared spectroscopy to determine the bulk chemical nature of each individual fraction, such as the extent of aromaticity, degree of polarity, etc. Based on this bulk information, model compounds representative of compounds in each fraction were selected and employed to develop the optimal high-resolution mass spectrometric analysis method for each fraction. An especially important aspect of this work was the optimization of the ionization method separately for each fraction by using appropriate model compounds so that most compounds in each fraction are ionized at approximately the same efficiency to generate only one type of stable ions (either molecular ions, protonated molecules or cations formed by hydride abstraction) containing the intact analyte molecule. This allows the DPF-MS method to produce reasonably accurate relative abundances for compounds present in each fraction, thereby making the method semi-quantitative. The compositional data thus obtained for the individual fractions were utilized to provide meaningful molecular level information for the crude oil. Inclusion of a mass balance for each fraction allows for data consolidation, which provides an accurate overall analysis of the crude oil, including average molecular weight and weight percentages of different compound classes.